Rudolf Schlechter’s South-American orchids V. Schlechter’s "network": Ecuador and Peru - Ossenbach, Carlos; Jenny, Rudolf (Lankesteriana: International Journal on Orchidology, 2021)
The fifth chapter of the series about Rudolf Schlechter’s South-American orchids introduces us to those botanists and orchid collectors who travelled and worked in Ecuador and Peru and supplied Schlechter with many of the new orchid species he described. As in previous chapters, the biographies and accomplishments of these travellers are preceded by brief geographical and historical outlines for each of these countries. It is worth mentioning that the lives and orchids of such prominent figures in the orchidology of South America as F.C. Lehmann, W. Hennis, E. Bungeroth and E. Ule, who collected in Ecuador and Peru, have already been mentioned in previous chapters and are therefore omitted here. Keywords/Palabras clave: biography, biografía, history of botany, historia de la botánica, Orchidaceae For accessing the high-resolution PDF, please follow this link: https://n9.cl/836os